THE EFFECT OF GOOD UNIVERSITY GOVERNANCE ON EMPLOYEE PERFORMANCE WITH EMPLOYEE ENGAGEMENT AS A MODERATING VARIABLE(A CASE STUDY AT UNIVERSITY X) - Ardin Etika Nur Andarisasi; Veronica Christina (Universitas Tulungagung, 2026)
This study seeks to evaluate the impact of Good University Governance (GUG) on employee performance and investigate the moderating function of employee engagement at University X. The use of effective governance concepts, including openness, accountability, responsibility, and equity, is thought to foster a favorable work environment and enhance employee performance.This study utilizes a quantitative methodology, gathering data via questionnaires administered to staff at University X. The data were examined through validity and reliability assessments, classical assumption evaluations, and hypothesis testing to ascertain the correlations among variables.The findings demonstrate that Good University Governance positively and significantly influences employee performance. This indicates that improved application of governance principles results in enhanced employee performance. Moreover, employee engagement has been demonstrated to regulate the association between GUG and employee performance, with elevated levels of employee engagement amplifying the positive impact of GUG on performance. This study indicates that raising governance quality in higher education institutions and increasing employee engagement are essential for improving employee performance and efficiently attaining organizational objectives.